2021
DOI: 10.3390/molecules26061553
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Volatile Compounds and Expression of Related Genes in Fruit from Two Apple Cultivars during Different Developmental Stages

Abstract: Aromatic volatile compounds are important contributors to fruit quality that vary among different cultivars. Herein, headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry was used to determine changes in volatile compounds and related gene expression patterns in “Ruixue” and “Fuji” apples (Malus domestica Borkh.) during fruit development and maturation. Volatile compounds detected in the fruit of both cultivars exhibited similar trends across different developmental stages. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“… 21 , 22 The aroma derivatives formed through the LOX pathway are primarily synchronized by fatty acid desaturase (FAD), LOX, hydroperoxide lyase (HPL), alcohol dehydrogenase (ADH), and alcohol acyltransferase (AAT) coding genes. 23 , 24 In recent years, many candidate genes involved in this pathway have been identified in apple, 25 mango, 26 grapes, 27 pear, 28 peach, 29 tomato, 30 strawberry, 31 and kiwifruit. 32 β-oxidation, as well as amino acids such as alanine, valine, leucine, isoleucine, and phenylalanine, is a potential precursor of acyl-CoAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 22 The aroma derivatives formed through the LOX pathway are primarily synchronized by fatty acid desaturase (FAD), LOX, hydroperoxide lyase (HPL), alcohol dehydrogenase (ADH), and alcohol acyltransferase (AAT) coding genes. 23 , 24 In recent years, many candidate genes involved in this pathway have been identified in apple, 25 mango, 26 grapes, 27 pear, 28 peach, 29 tomato, 30 strawberry, 31 and kiwifruit. 32 β-oxidation, as well as amino acids such as alanine, valine, leucine, isoleucine, and phenylalanine, is a potential precursor of acyl-CoAs.…”
Section: Introductionmentioning
confidence: 99%
“…Research evidence showed that fatty acids and amino acids are the major precursors of aroma biosynthesis in most fruit species . Specifically, fatty-acid-regulated lipoxygenase (LOX) and β-oxidation processes are the major determinants for the biosynthesis of aldehydes, alcohols, and straight-chain esters. , The aroma derivatives formed through the LOX pathway are primarily synchronized by fatty acid desaturase (FAD), LOX, hydroperoxide lyase (HPL), alcohol dehydrogenase (ADH), and alcohol acyltransferase (AAT) coding genes. , In recent years, many candidate genes involved in this pathway have been identified in apple, mango, grapes, pear, peach, tomato, strawberry, and kiwifruit . β-oxidation, as well as amino acids such as alanine, valine, leucine, isoleucine, and phenylalanine, is a potential precursor of acyl-CoAs. , Later on, acyl-CoAs leads to the biosynthesis of aroma volatiles through the functional mechanism of acyltransferase, decarboxylation, oxidation, and reduction-related enzymes .…”
Section: Introductionmentioning
confidence: 99%
“…Our observations of volatile compounds are in accordance with the reported data on enzyme regulation in Golden Delicious and Jonagold apples, particularly for the activities of the lipoxygenase (LOX) [ 40 ] and alcohol dehydrogenase (ADH) [ 41 ]. Additionally, the amino transferase activity is also reported to increase during fruit development in Fuji apples, and thus the increase of branched alcohols [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, advanced ripeness of the fruits leads to an increased bioavailability of precursors leading to high ester concentrations and thus to high fruitiness of the ripe products [ 44 ]. On the other hand, many enzymes involved in the bio-formation of esters, such as ADH and LOX, demonstrate higher activity in mature fruits compared to unripe Fuji and Ruixue samples [ 42 ]. With respect to the current harvest recommendation, the given correlations in Figure 2 show very clearly that for the formation of fruitiness, Crimson Crisp apples require longer on-tree ripening than approx.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptome and metabolome analyses showed that LOXs could lead to differences in the strength of the “grassy” aroma between two white-fleshed pitaya cultivars [ 47 ]. Studies showed that the LOX enzyme activity in apple [ 48 , 49 , 50 , 51 ], strawberry [ 52 , 53 ], peach [ 28 , 54 ], pear [ 55 ], and grapes [ 56 ] was directly related to fruit ripening and fruit aroma formation. TomLOXC was confirmed to be involved in the production of fatty-acid-derived C5 and C6 flavor compounds [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%